(untitled) (MIST International Journal of Science and Technology, 2023)
The response over the low-velocity impact of various shape impactors on a glass fiber reinforced polymer composite has been numerically analyzed with a hemispherical, flat, partially flat and truncated shaped impactor used to analyze the behavior of resistance of a GFRP composite at various speeds. The numerical analysis was carried out using finite element analysis software, ABAQUS (Dynamic/Explicit). To assess the response of the composite laminates while impacting, finite element models were developed. The Hashin failure criteria were used to represent braided glass-fiber reinforced composite plate damage. Regarding projectile shape, the impact reaction of the composite was examined. The results also show that the mechanical response of woven glass fiber polymer composite under low-velocity projectile impact largely depends on the impactor’s nose shape and the velocity of the impactor. MIJST, Vol. 11, June 2023 : 31-38 DOI: https://doi.org/10.47981/j.mijst.11(01)2023.375(31-38)